Partisanship Versus Democracy: Voting in Turkey's Competitive Authoritarian Elections. (November 2022) - Demirel-Pegg, Tijen; Dusso, Aaron
Do voters care about anti-democratic behavior by their leaders? While political pundits and academics often hope that they do, there has been little research that tests the effects that specific anti-democratic actions have on voters during elections. This is because there are few clear instances where violations of democratic norms are so visible to the average voter that one would expect it to have an effect, above and beyond traditional predictors of the vote. However, the recent elections in Turkey offer a unique opportunity to test the effect that nullifying an entire election (an unequivocal violation of democratic norms) has on voters. We do exactly that with a survey of voters following the election re-do. We find that even in such an extraordinary circumstance, voters rely on standard voting drivers like partisanship, rather than concern for the functioning of democracy itself. Ultimately, our findings have important implications for voting in competitive authoritarian regimes, as they fail to show that anti-democratic behavior is punished.